2018
DOI: 10.21270/archi.v7i7.3040
|View full text |Cite
|
Sign up to set email alerts
|

Análise da associação entre oclusão e disfunção temporomandibular: estudo clínico

Abstract: Com o objetivo de verificar a associação entre a oclusão e a disfunção temporomandibular (DTM), o presente estudo se propôs a avaliar a oclusão com relação às Seis Chaves de Oclusão de Andrews, os guias de desoclusão e os contatos dentais, em pacientes com a presença associada ou não de DTM, seguindo o Research Diagnostic Criteria(RDC). Foram incluídos 18 pacientes, de ambos os sexos, com faixa etária entre 21 e 61 anos, os quais participaram da fase clínica (análise do RDC) e da fase laboratorial (análise da … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…When referring to onset or perpetuating variables of TMD and headache, it is important to mention that the literature shows no connection between TMD/headache and orthodontic treatment. In addition, there is inadequate data to support the idea that occlusal adjustment or orthodontic treatment of malocclusion can help prevent TMD [60][61][62].…”
Section: Psychological Inflexibility In Chronic Painmentioning
confidence: 99%
See 1 more Smart Citation
“…When referring to onset or perpetuating variables of TMD and headache, it is important to mention that the literature shows no connection between TMD/headache and orthodontic treatment. In addition, there is inadequate data to support the idea that occlusal adjustment or orthodontic treatment of malocclusion can help prevent TMD [60][61][62].…”
Section: Psychological Inflexibility In Chronic Painmentioning
confidence: 99%
“…Although studies have shown that occlusion is important not only for the development of TMD but also for its treatment [90][91][92], others stated that different types of malocclusion might be linked to headache [12,14,62,[90][91][92][93][94]. However, most of the literature does not consider these factors as major aspects in TMD aetiology, but they cannot be completely dissociated [60][61][62]93,94].…”
Section: Pain Management Of Tmd-headachementioning
confidence: 99%